Digital volunteer services in emergency situations: Typological characteristics, advantages, and challenges - Yongzhong Sha; Xingfei Wei; Chunhua Niu; Yongbao Zhang; Lu He (Data Science and Management)
Volunteer engagement in emergency management, focusing on mitigating adverse consequences, has attracted scholarly and practitioner attention. Digital volunteering helps overcome the limitations of traditional on-site volunteering through extensive volunteering opportunities in emergency management. This study utilizes a case text analysis and interviews to investigate and categorize digital volunteer services in emergency scenarios. Based on two key dimensions—direct recipients of volunteer services and the nature of the services rendered—the study presents four types of digital volunteer services: bridging, supportive, complementary, and collaborative. Moreover, it delineates eight role archetypes digital volunteers assume in emergency response situations along with their primary service contributions. Compared to conventional on-site volunteer services, digital volunteer services offer unique advantages while facing specific challenges. Finally, this study offers recommendations in four dimensions for the robust development of digital volunteer services, contributing to more effective and sustainable emergency management practices.